(untitled) (IAHS Medical Journal, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is increasing worldwide in particular in Bangladesh. Early diagnosis of T2DM, followed by proper management will help in leading a cardiovascular event free life. Although the event of cardiovascular profile in new T2DM patients is limited. This study aims to evaluate the extent of Cardiovascular disease (CVD) risk factors in newly diagnosed T2DM patients in Chattogram. Materials and methods: A cross sectional observational study was conducted during the period from January to May 2025 to evaluate clinical laboratory and socio-demographic parameters of 528 newly diagnosed T2DM patients aged 30 years and above. The cardiovascular related risk factors were assessed collecting data by face to face interview and from history, pathological records done during diagnosis of diabetes mellitus. Data were compiled and assessed by SPSS version 23. Chi square test was done to see association between socio demographic characteristics and risk factors. Results: Out of 528 diabetic patients, majority 192(36.4%) were diagnosed at age between 51-60 years. Females were predominant 307(58.1%). 303(57.4%) were service holder, 172(32.6%) belonged to lower middle class and 173(32.8%) passed primary school. 171(32%) of the patients lead sedentary life style and 431(81.6%) were non smoker. 185(35%) were overweight and 198(37.5%) were obese. 464(87.8%) had family history of DM, 263(49.8%) had hypertension and 210(39.7%) had high cholesterol level. This study revealed significant association of diabetes mellitus with education, occupation, physical activity, BMI and hypertension (p value <0.00%) Conclusions: Less physical activity, high BMI and hypertension increases the morbidity of diabetes mellitus. IAHS Medical Journal Vol 8(1), June 2025; 39-43